PENGARUH BOPO, NPF, ROA DAN INFLASI TERHADAP ASET PERBANKAN SYARIAH DI INDONESIA - Annisa Millania; Rofiul Wahyudi; Ferry Khusnul Mubarok; Julia Noermawati Eka Satyarini (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
The growth of Islamic banking assets in Indonesia has experienced a very significant growth. The purpose of this study is to analyze the internal and external factors that influence this growth. This research method uses a quantitative design with a causal approach. Internal data sources use Islamic bank financial reports for the 2016-2020 period and external data, namely inflation. The sampling technique was determined by purposive sampling method, namely 7 Islamic Commercial Banks. The results showed that the internal factors NPF and ROA had no significant effect on assets. In contrast, BOPO has a significant effect on assets. External factors, inflation have a significant effect on Islamic banking assets.